Pengembangan Multimedia Interaktif Berbantuan Articulate Storyline di Sekolah Dasar - Maharani, Jihan; Firman, Firman; Lisa Aditya Dwiwansyah Musa (South Sulawesi Education Development, 2024)
This research explores the needs analysis, validity, practicality and effectiveness of interactive media with the theme